MENYOAL KREATIFITAS REDESAIN KEMASAN TRADISIONAL INDONESIA - Lukitasari, Evelyne Henny (KEMADHA, 2012)
Packaging design not only serves as a wrapper but also as a medium for the promotion of a product through a visual language that promotes creativity as a weapon in creating his works. Creativity in addition to helping create beautiful work, a new, unique but able to provide solutions to the needs of society in a culture contemporaries. This is intended to revitalize traditional packaging marginalized into the packing has a sale value, competitiveness with modern packaging and has prestige.